Maria Edgeworth's Political Lives. Issue 6 (1st November 2020) - Manly, Susan
ABSTRACT: This essay examines Maria Edgeworth's rewriting of masculine political power and visibility, focusing on collaborations with her father and brother on explicitly political projects to show how she gained a political life of her own through the personae and authorial disguises she adopted in these "partnership" works. Far from simply "illustrating and manufacturing" her father's ideas, as she claimed, and contrary to her assertion that "all the general ideas [in her writings] originated with him, " Edgeworth herself often designed and directed her "collaborative" publications. She thus assumed the dress of a masculine political life in print form, and was to some extent the inventor of her father's public and political identity. This argument runs contrary to views of Edgeworth as simply her father's copyist, and complicates the "question of authorship" identified as a central problem in Marilyn Butler's biography of Edgeworth and much subsequent criticism. I suggest that while Edgeworth drew on her father's conversation and liberally shared stock of experiences and information, we can find evidence of her own political philosophy in the works written by her under male names, culminating in her editing and rewriting of her father's "life" in the Memoirs of Richard Lovell Edgeworth .